2023
DOI: 10.1155/2023/3634726
|View full text |Cite|
|
Sign up to set email alerts
|

Biomolecule Protective and Photocatalytic Potential of Cellulose Supported MoS2/GO Nanocomposite

Abstract: In the current study, cellulose/MoS2/GO nanocomposite has been synthesized by a hydrothermal method. Reports published regarding efficiency of Mo and graphene oxide-based nanocomposites for environmental remediation motivated to synthesize cellulose supported MoS2/GO nanocomposite. Formation of nanocomposite was initially confirmed by UV-visible and FTIR spectroscopic techniques. Particle size and morphology of the nanocomposite were assessed by scanning electron microscopy (SEM), and it was found having parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In addition, nanocellulose also has more applications in photocatalytic degradation. Muhammad et al [15] synthesized cellulose /MoS2/GO nanocomposites, which can be used as a nanocatalyst for the removal of 4-nitrophenol found in pharmaceutical efuent and dyes from textile industry wastewater. Neha et al [16] prepared cellulose supported Bismuth vanadate (Cel/BiVO4) nanocomposites with significant photocatalytic activity from waste biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nanocellulose also has more applications in photocatalytic degradation. Muhammad et al [15] synthesized cellulose /MoS2/GO nanocomposites, which can be used as a nanocatalyst for the removal of 4-nitrophenol found in pharmaceutical efuent and dyes from textile industry wastewater. Neha et al [16] prepared cellulose supported Bismuth vanadate (Cel/BiVO4) nanocomposites with significant photocatalytic activity from waste biomass.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%